Flattening The Epidemic Curve from a Statistical and Epidemiological Approach in Malaysia - Nur Aifiah Ibrahim (Fakultas Kedokteran Universitas Lambung Mangkurat, 2023)
Abstract: Epidemic curves will help decision-makers and the public to give a picture and pattern of the outbreak. It will create a path to explore the epidemiology of Covid-19. One of the highlights is the onset of illness. One of the approaches is to track the progression of Covid-19 in Malaysia. In Malaysia, the numbers and figures began to convey a message about the epidemic progression and put in efforts to stop the pandemic. The disease pattern grows exponentially. Hence, proper lines of rapid strategies are there to flatten the curve.